2020
DOI: 10.1136/vr.105805
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of a targeted smartphone application to aid veterinary students in calculating constant rate infusions and perioperative fluid drip rates

Abstract: BackgroundTo compare the utility of a targeted smartphone application (TSPA) with a non-programmable calculator (NPC) when calculating fluid drip rates (FDR) and constant rate infusions (CRIs).MethodsIn a prospective randomised clinical study, 48 fourth-year veterinary students entered one of four parallel groups involving two mock scenarios: fentanyl calculation using an NPC followed by lidocaine calculation using a TSPA, fentanyl (TSPA) followed by lidocaine (NPC), lidocaine (NPC) followed by fentanyl (TSPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Calculation errors occur mainly from unit conversion errors (eg, mg to mcg) and errors when multiplying or dividing. 24 Evidence from physician prescriptions identified calculation errors as stemming from insufficient basic mathematical skills. 25 This may highlight a critical gap in healthcare practitioner course curricula: the need for teaching and assessing drug calculation skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation errors occur mainly from unit conversion errors (eg, mg to mcg) and errors when multiplying or dividing. 24 Evidence from physician prescriptions identified calculation errors as stemming from insufficient basic mathematical skills. 25 This may highlight a critical gap in healthcare practitioner course curricula: the need for teaching and assessing drug calculation skills.…”
Section: Discussionmentioning
confidence: 99%
“…In human pediatric practice, it is reported that 85% (35/41) of anesthetists were unable to calculate a dopamine infusion for a pediatric patient. 27 As a strategy to reduce calculation errors, smartphone applications have been described as being successful in facilitating anesthesia management and reducing errors by veterinary students 24 and human anesthesia providers. 28 Additionally, automated dose calculation tools exist and may represent an accessible option for veterinary patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology, including electronic prescribing and smart infusion pumps, has substantially improved medication safety in human medicine 23 . Similarly, in 1 veterinary study, medication dosing errors were reduced by 52% when veterinary students used a targeted smartphone application instead of a calculator to determine continuous infusion and fluid drip rates 24 . These are promising outcomes that should not only be disseminated across the profession for broader adoption, but also invested in to further mitigate safety risks in veterinary environments.…”
Section: The Work Has Already Begunmentioning
confidence: 99%